Analysis of Thought and Language "Dari Pada Laba Dou Tahopu laba Dana": Psycholinguistic Study - Suryaningsih, Lili; Sukarddin, Sukarddin (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Psycholinguistics is a theory between psychology and linguistics. These theories are very different but they are related in examining language as a formal object. This article discusses linguistics, psycholinguistics and their studies. The word psychology discusses the science that studies the human soul in an abstract manner, while the word linguistics discusses language as an object of study. For this reason, psycholinguistic theory can describe the psychological processes that take place when someone utters the sentences they hear when communicating and this language ability can be obtained from humans. Therefore, the motto of profit dou tahopu profit funds is a big mistake because it has a negative value or can harm other people, either in the form of attitudes/actions, or actions that violate the law in the Islamic religion in measuring obsessions caused by desires that exceed one's abilities.